Hypsagonus quadricornis - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Hypsagonus quadricornis (Valenciennes, 1829). Fourhorn Poacher . To 12 cm (4.7 in) TL (Tokranov and Orlov 2004). Northern Japan and Sea of Okhotsk, to Commander–Aleutian Chain, and Bering Sea (Mecklenburg et al. 2002), to northeastern Chukchi Sea as far north as 71°01’N, 164°52’W (Mecklenburg et al. 2016), to Puget Sound, Washington (Eschmeyer and Herald 1983). Benthic; depth: intertidal to 452 m (1,483 ft) (Mecklenburg et al. 2016). The species name is often attributed to Cuvier, but Valenciennes provided both the species name and the description; the full citation is Valenciennes in Cuvier & Valenciennes, 1829 (Sheiko 1993; see also Mecklenburg et al. 2002, Sheiko and Mecklenburg 2004). Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 130, DOI:10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008